Proportion of Human Resources and Material and Equipment Financing in Housing Projects - Siswoyo, Mochammad Rico; Gunasti, Amri; Kuryanto, Totok Dwi (International Applied Science, 2023)
Improper distribution of human resources and equipment proportions in a construction project will result in an increase in the cost budget, therefore it is necessary to deepen through research regarding the proportion of construction project resources. This research aims to calculate human and material resources and equipment in housing construction projects using the comparative method. Use of the comparison method to compare the differences in 2 or more groups in different samples. The proportion results for human resources in Grand Permata Kaliurang housing is 19.64 percent and in Diamond City housing 19.88 percent, while the proportion of material resources in Grand Permata Kaliurang housing is 79.21 percent and in Diamond City housing is 78.84 percent and for equipment resources at Grand Permata Kaliurang housing 1.15 percent and for Diamond City housing 1.28 percent.